Determining the Pancreatic Arginase Activity and \(α\)-Amylase Levels in Patients with Type 2 Diabetes and Alcoholic Pancreatitis - Méndez, José D.; Haro, Roberto De; Méndez-Valenzuela, Verna; Ble-Castillo, Jorge L.; Rubio, Hector O. (Challenging Issues on Environment and Earth Science Vol. 5, 2021)
Arginase, a regenerative enzyme located in the endocrine pancreas, is involved in insulin metabolism and regenerative processes during polyamine formation. Pancreatic damage has been linked to high levels of \(α\)-amylase. The aim of this study was to determine the function of arginase and \(α\)-amylase in the pancreas of people with type 2 diabetes and those who had alcohol-induced acute pancreatitis. Patients with type 2 diabetes mellitus or acute pancreatitis without pancreatic diabetes had their arginase and \(α\)-amylase activities assessed in pancreatic tissue. The findings were compared to the results of a control group. Our findings indicate that diabetics' pancreas have higher arginase activity than controls, while pancreatitis patients' tissues have lower arginase activity (P <0.05). The activity of a-amylase was higher in type 2 diabetes patients' pancreases than in acute pancreatitis patients' pancreases. Rather than being the source of damage mediators, elevated arginase activity in type 2 diabetes patients may be linked to an effort to reclaim endocrine pancreatic function. Because there is acinar damage in pancreatitis with a subsequent release a \(α\)-amylase, this enzyme was higher in pancreatic tissue of diabetics than in pancreatic tissue of pancreatitis patients.